A design programme for dilute phase pneumatic conveyors - Wodrich, Karsten H. K. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 1997.